2004
DOI: 10.4028/www.scientific.net/msf.455-456.801
|View full text |Cite
|
Sign up to set email alerts
|

Free Formaldehyde Determination Using HPLC

Abstract: Release of formaldehyde from durable press treated fabrics is a problem for human health and safety because formaldehyde is suspected to be carcinogen. The accuracy of the standard test method for the free formaldehyde determination, Japan Law 112, depends on the formaldehyde content of the sample. The formaldehyde contents below 20 µg/g cannot be shown to be caused by formaldehyde. The detection of low formaldehyde contents is important particularly in some fields, like children clothing, so the High Performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
0
12
1
Order By: Relevance
“…RR198 can thus be decomposed by radicals in US-based systems. Voncina and Majcen-LeMarechal [8] proposed that H 2 O 2 addition accelerates the reaction rate of the US system; however, this study did not support this observation. Most of the H 2 O 2 may be present not inside the cavitation bubbles, rather in the bulk solution, because of its high solubility in water and its low volatility.…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…RR198 can thus be decomposed by radicals in US-based systems. Voncina and Majcen-LeMarechal [8] proposed that H 2 O 2 addition accelerates the reaction rate of the US system; however, this study did not support this observation. Most of the H 2 O 2 may be present not inside the cavitation bubbles, rather in the bulk solution, because of its high solubility in water and its low volatility.…”
Section: Resultscontrasting
confidence: 81%
“…Enhanced degradation of RR198 is difficult to achieve by adding H 2 O 2 to the US system. Voncina and Majcen-Le-Marechal [8] suggested that the effect of H 2 O 2 addition on decolorization depends on the type of dye. The degradation rate of organics typically increases with the H 2 O 2 dosage up to a critical value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Textiles are often finished with formaldehyde-containing chemicals, which can provide crease resistance, flame retardance, and dimensional stability. [3,4] Its contact directly with human skin may cause an irritant effect on the mucous membrane. If inhaled, emitted formaldehyde may cause inflammation of the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…If inhaled, emitted formaldehyde may cause inflammation of the respiratory tract. [3,4] A rapid and sensitive method for the determination of formaldehyde in textile samples at low levels is required.…”
Section: Introductionmentioning
confidence: 99%